2012
DOI: 10.25026/jtpc.v2i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Metabolit Sekunder dan Aktivitas Antibakteri Ekstrak Daun Sungkai (Peronema canescens JACK.) terhadap Beberapa Bakteri Patogen

Abstract: A research which identification of secondary metabolites and antibacterial activity test from methanol exstract of leaf Sungkai (Peronema canencensJack

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 0 publications
0
23
0
24
Order By: Relevance
“…Somehow, it also uses for women after childbirth and as a mouthwash to prevent toothache. 11,12 Previous studies were reported that P. canescens) contain several bioactive compound, and the bioactive compound might act as antimalarial, antiplasmodial, 13 antibacterial, 14 analgesic, and immunomodulator. 15 P. canescens leaves contains bioactive compound such as flavonoids, alkaloids, steroids, tannins, phenol, and saponins.…”
Section: Introductionmentioning
confidence: 99%
“…Somehow, it also uses for women after childbirth and as a mouthwash to prevent toothache. 11,12 Previous studies were reported that P. canescens) contain several bioactive compound, and the bioactive compound might act as antimalarial, antiplasmodial, 13 antibacterial, 14 analgesic, and immunomodulator. 15 P. canescens leaves contains bioactive compound such as flavonoids, alkaloids, steroids, tannins, phenol, and saponins.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid memiliki aktivitas untuk menghambat pertumbuhan bakteri dengan cara mendenaturasi protein yang menyebabkan terhentinya aktivitas metabolisme sel bakteri, dengan terhentinya aktivitas metabolisme mengakibatkan kematian pada sel. Flavonoid lipofilik dapat membentuk senyawa kompleks dengan protein ekstraseluler sehingga mengganggu integritas membran sel bakteri [33,[35][36]. Tanin diduga dapat mengerutkan dinding sel sehingga mengganggu permeabilitas sel bakteri [35].…”
Section: Hasil Uji Aktivitas Antibakteriunclassified
“…Flavonoid lipofilik dapat membentuk senyawa kompleks dengan protein ekstraseluler sehingga mengganggu integritas membran sel bakteri [33,[35][36]. Tanin diduga dapat mengerutkan dinding sel sehingga mengganggu permeabilitas sel bakteri [35]. Selain itu, tanin diduga mengganggu kerja DNA gyrase, yaitu enzim yang berperan dalam replikasi DNA [37].…”
Section: Hasil Uji Aktivitas Antibakteriunclassified
See 1 more Smart Citation
“…The P. canescens extract has been used for a long time as an herbal medicine to treat toothache, cold, fever, and ringworm [21]. The methanol extract of P. canescens leaves is known to contain secondary metabolites such as alkaloids, flavonoids, terpenoids, steroids, and tannins [22]. In addition, studies have shown that the extract of young leaves of P. canescens has good activity as an herbal medicine and a dosage of 0.5625 mg kg w/w can decrease the mice body temperature by up to 29% [23].…”
Section: Introductionmentioning
confidence: 99%